2021
DOI: 10.1002/jnr.24822
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral motor pathways to the lower limb after stroke: Insights and opportunities

Abstract: Stroke-related damage to the crossed lateral corticospinal tract causes motor deficits in the contralateral (paretic) limb. To restore functional movement in the paretic limb, the nervous system may increase its reliance on ipsilaterally descending motor pathways, including the uncrossed lateral corticospinal tract, the reticulospinal tract, the rubrospinal tract, and the vestibulospinal tract. Our knowledge about the role of these pathways for upper limb motor recovery is incomplete, and even less is known ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 112 publications
0
20
0
Order By: Relevance
“…However, it is possible that this activity is related to postural stabilization of the body during reaching. Indeed, extrapyramidal pathways such as the reticulospinal track have a prominent ipsilateral projection associated with postural control ( Cleland and Madhavan, 2021 ), and these pathways receive cortical input. We aimed to reduce postural demands in our task by having the participants seated in an upright hospital bed with the back fully supported; nonetheless, there are surely postural shifts associated with the reaching movement.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that this activity is related to postural stabilization of the body during reaching. Indeed, extrapyramidal pathways such as the reticulospinal track have a prominent ipsilateral projection associated with postural control ( Cleland and Madhavan, 2021 ), and these pathways receive cortical input. We aimed to reduce postural demands in our task by having the participants seated in an upright hospital bed with the back fully supported; nonetheless, there are surely postural shifts associated with the reaching movement.…”
Section: Discussionmentioning
confidence: 99%
“…A potential explanation for this observation might derive from the limited number of crossing fibers in both tracts. 5,55 Considering the anatomical proximity of these crossing fibers and the relatively high overlap in explained variance in motor performance of all four tracts, one might assume that identical voxels were included in both tracts due to tracking inaccuracies or sampling biases. However, computing the overlap between all four masks yielded a negligible number of shared voxels.…”
Section: Anatomical Foundations Of Extrapyramidal Compensationmentioning
confidence: 99%
“…Stroke-related motor deficits are often caused by damage to the corticospinal tract (CST) and associated white matter (WM) changes are frequently assessed using anisotropy derived from diffusion MRI (dMRI). Studies commonly report a relationship between decreased anisotropy in various parts of the ipsilesional CST and the severity of motor impairment of the upper [1][2][3] and lower limbs [4][5][6] , highlighting anisotropy as a promising biomarker for motor recovery poststroke. 3 However, anisotropy measures have yet to find their way into clinical practice as individual predictions of motor impairment and recovery remain challenging for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…16 Recently, several studies have reported that the ipsilateral motor pathway plays a crucial role in compensating for motor impairment in both upper and lower limbs after subcortical brain injury. [17][18][19][20][21] This phenomenon can also be seen after spinal cord injury 22,23 ; therefore, ipsilateral M1 activation might help compensate for the functional deficit after movement disorders.…”
Section: Introductionmentioning
confidence: 99%